The appropriate use of non-steroidal anti-inflammatory drugs in rheumatic disease: opinions of a multidisciplinary European expert panel. Issue 5 (10th September 2010) - Burmester, Gerd; Lanas, Angel; Biasucci, Luigi; Hermann, Matthias; Lohmander, Stefan; Olivieri, Ignazio; Scarpignato, Carmelo; Smolen, Josef; Hawkey, Chris; Bajkowski, Adam; Berenbaum, Francis; Breedveld, Ferdinand; et al.
Abstract : Introduction: Given the safety issues of non-steroidal anti-inflammatory drugs (NSAID) and the robustness of guidelines, making treatment choices in daily clinical practice is increasingly difficult. This study aimed systematically to analyse the opinions of a multidisciplinary European expert panel on the appropriateness of different NSAID, with or without the use of a proton pump inhibitor (PPI), in individual patients with chronic rheumatic disease. Methods: Using the Research and Development/University of California at Los Angeles appropriateness method, the appropriateness of five (non-)selective NSAID with or without a PPI was assessed for 144 hypothetical patient profiles, ie, unique combinations of cardiovascular and gastrointestinal risk factors. Appropriateness statements were calculated for all indications. Results: All options without PPI were considered appropriate in patients with no gastrointestinal/cardiovascular risk factors. Cyclooxygenase-2 selective inhibitors (C2SI) alone and non-selective NSAID plus PPI were preferred for patients with elevated gastrointestinal risk and low cardiovascular risk. Naproxen plus PPI was favoured in patients with high cardiovascular risk. For the combination of high gastrointestinal/high cardiovascular risk the use of any NSAID was discouraged; if needed, naproxen plus PPI or a C2SI plus PPI could be considered. Discussion: The panel results may support treatment considerations at the level of individual patients, according to their gastrointestinal/cardiovascular risk profile.